The root tantra and the explanatory tantra from the secret quintessential instructions on the eight branches of the ambrosia essence tantra = Bod kyi bso ba rig pa'i rgyud ba'i las rtsa ba'i rgyud dang Bshad pa'i rgyud ces bya ba bzhugs so - Yon-tan-mgon-po 1126-1202 (Men-Tsee-Khang Publications, 2015)
Commentaries on Rtsa rgyud and Bśad rgyud of the four fundamental Tibetan medicinal treatises